Neuroimaging Links Between Heart Failure and Depression—A Narrative Review - Giacomo Deste; Carlo Lombardi; Roberto Gasparotti; Antonio Vita; Daniele Corbo (Brain Sciences, 2024)
Background and objective: It is commonly known that there is a connection between heart disease and depression symptoms. Compared to heart failure patients without concurrent depression, those with depressive symptoms are more likely to have longer hospital stays and more outpatient visits following discharge. Although the exact neurobiological mechanisms causing the correlation between heart disease and depression symptoms are unknown, it is thought that vascular abnormalities may be a major factor. The purpose of this review was to examine the connection between brain networks linked to depression and heart failure (HF). Methods: PRISMA guidelines were followed. We included studies that reported both heart failure as well as depression and neuroimaging. Results: We identified 159 papers, but only 12 articles were included. Our findings show that reduced cerebral blood flow (CBF) following HF, along with other contributing factors such as chronic inflammation and neurovascular dysfunction, can lead to significant brain tissue damage and disruption of neural networks. The resulting alteration in the brain increases the risk of developing depression, as the neural circuits responsible for emotional regulation become compromised. Conclusions: Individuals with heart failure (HF) exhibit reduced regional cerebral blood flow across multiple brain areas, many of which are critical for mood regulation and are commonly implicated in depression, such as the left frontal cortex and right hippocampus.